Motivasi Kerja Karyawan dalam Rangka Meningkatkan Kinerja di Dinas Kebudayaan dan Pariwisata di Kota Surabaya - Damayanti, Devina Fitri; Cahyani, Intan Dwi; Nurrachma, Amanda Laila (Ikatan Da'i Indonesia, 2024)
This research aims to find out and describe how work culture is implemented and what motivates employees to improve their work at the Surabaya City Tourism and Culture Office. This can be seen from various factors, namely, intrinsic (internal) factors and extrinsic (external) factors. In obtaining quality Human Resources, the work process runs smoothly, and the work results are in accordance with what is desired must come from the behavior of each individual. This means that in forming a work culture and work motivation from leaders or employees it must be consistent with good coordination so that the vision and mission of the organization can be realized in accordance with what is desired. This research uses a qualitative descriptive research method. Data collection used interview techniques and carried out observations through purposive sampling techniques. The results of the research show that employee motivation has a big influence on improving the performance of employees at the Surabaya City Culture and Tourism Office. This can be seen from intrinsic (internal) factors and extrinsic (external) factors. Intrinsic (internal) factors are the achievements of the employee himself. Meanwhile, extrinsic (external) factors are in the form of communication relationships experienced between employees and superiors. So it can be concluded that employee work motivation must be maintained from an early age in order to achieve maximum results in accordance with the goals of the organization itself.